Alcohol consumption, physical activity, and chronic disease risk factors: a population-based cross-sectional survey - Djoussé Luc; Ding Eric L; Mukamal Kenneth J (BMC, 2006)
Abstract Background Whether the association of alcohol consumption and cardiovascular disease is the product of confounding and the degree to which this concern applies to other behaviors are unclear. Methods Using the 2003 Behavioral Risk Factor Surveillance System, a population-based telephone survey of adults in the US, we compared chronic disease risk factors between 123,359 abstainers and 126,674 moderate drinkers, defined as intake of ≤ 2 drinks per day among men and ≤ 1 drink per day among women, using age- and sex- and multivariable-adjusted models. We also compared sedentary and active individuals, defined as moderate physical activity ≥ 30 minutes per day for ≥ 5 days per week, or vigorous activity for ≥ 20 minutes per day on ≥ 3 days. Results Chronic disease risk factors and features of unhealthy lifestyle were generally more prevalent among abstainers than drinkers in age- and sex-adjusted analyses, but these differences were generally attenuated or eliminated by additional adjustment for race and education. For low fruit and vegetable intake, divorced marital status, and absence of a personal physician, adjustment for race and education reversed initially positive age- and sex-adjusted associations with abstention. Comparison of sedentary and active individuals produced similar findings, with generally lower levels of risk factors among more physical active individuals. Conclusion The differences between abstainers and drinkers are attenuated after adjustment for limited sociodemographic features, and sedentary and active individuals share a similar pattern. Although observational studies of both factors may be susceptible to uncontrolled confounding, our results provide no evidence that moderate drinking is unique in this regard. Ultimately, randomized trials of all such lifestyle factors will be needed to answer these questions definitively.